PENDEKATAN KLINIS DAN STRATEGI MANAJEMEN TERKINI PADA NYERI PUNGGUNG BAWAH TIPE CAMPURAN - Tama, Whisnu Nalendra; Yudiyanta (PERDOSNI, 2025)
Low back pain (LBP) is one of the most common musculoskeletal complaints and a frequent cause of chronic pain. It has a complex etiology which may involve overlapping pain mechanisms, including nociceptive, neuropathic, and nociplastic, resulting in a mixed pain condition. Several studies have shown that neuropathic components are present in a significant proportion of LBP cases, even in the absence of clear radicular symptoms. Understanding the pathophysiological mechanisms underlying mixed pain is essential, including both peripheral and central sensitization processes, as well as interactions between neural and non-neural structures such as the intervertebral disc and facet joints. The clinical approach to LBP requires comprehensive history taking and physical examination, including identification of pain characteristics and red flags, along with the use of neuropathic pain screening questionnaires such as PainDETECT, Douleur Neuropathique en 4 (DN4), and ID Pain. Supporting investigations, including Magnetic Resonance Imaging (MRI) and electrophysiological studies, should be performed as indicated to determine the etiology and degree of nerve involvement. Management of mixed-type LBP should be multimodal, encompassing nonpharmacological therapies such as patient education, medical rehabilitation, and postural correction, as well as pharmacological treatments combining anti-inflammatory and neuropathic pain agents. Although such combination therapy is theoretically beneficial, supporting clinical evidence remains limited and warrants further research. Increasing clinicians’ awareness of the possibility of mixed pain in LBP is crucial for determining more optimal and precise therapeutic strategies to improve patient clinical outcomes. Keywords: low back pain, mixed pain, central sensitization, multimodal management, mechanism-based therapy